(untitled) (Indian Journal of Nematology, 2024)
For almost half of the world’s population, rice is a staple food. In addition to the numerous challenges, rice production worldwide is seriously threatened by the rice root-knot nematode (RRKN), Meloidogyne graminicola. Developing resistant rice varieties is a priority for sustainable agriculture since M. graminicola infestations cause substantial yield losses and economic consequences. Understanding the intricate host-pathogen interaction between rice and rice root-knot nematode is fundamental for effective resistance breeding. Recent molecular studies have shed light on the underlying mechanisms, providing valuable insights into potential targets for genetic manipulation. Numerous resistance genes have been identified in rice, conferring varying resistance levels against RRKN. These genes, discovered through conventional breeding and advanced molecular techniques, serve as the foundation for developing resistant rice cultivars. The integration of marker-assisted selection techniques has expedited the breeding process by enabling the identification and selection of plants with desirable resistance traits more efficiently. This method proved significant in facilitating the development of rice variants resistant to RRKN. Advancements in genetic engineering techniques, such as CRISPR-Cas9, have opened new avenues for precise manipulation of the rice genome to enhance resistance against RRKN. The potential of transgenic approaches in creating durable resistance needs to be further explored while addressing regulatory and ethical considerations. Despite significant progress, challenges persist in developing resistant rice varieties with durable and broad-spectrum resistance against RRKN. The progress in resistance breeding against rice root-knot nematode marks a crucial step toward sustainable rice production. Continued research efforts, incorporating cutting-edge technologies and collaborative initiatives, are essential for addressing the complexities of RKN resistance and ensuring global food security through improved rice varieties. This paper provides a concise overview of the progress made in resistance breeding against RRKN, highlighting key advancements and challenges in this crucial area of research.